Teologi Diakonia dalam Merespon Kemiskinan dan Penyandang Disabilitas - Simamora, Kornelia Agatha; Sinaga, Lamria (JURNAL DIAKONIA, 2022)
This paper is a study analytical literature role diakonia in respond poverty and disability. In analyze study this writer collect poverty data and disability from study earlier. For next writer analyze it from various source book and then expose role theology diakonia in respond problem poverty and disability. As for results from study this namely: diakonia is a calling for share life to fellow specifically they clan poor and the oppressed because a limitations physique nor mentally. Experienced people limitations physique and mentally called with disabled disability that is those who have disabled in a manner biological and physical cause sufferer disturbed in to do activity every day. Situation this is necessary responded with method apply the diakonia which one duty from church. The church not only to do service in a manner routine will but must open eye for those who experience suffering as well as presenting the kingdom of God in the midst clan poor and disabled disability.